The local knowledge of freshwater fishes among Lundayeh ethnic in Long pasia, Sabah, Malaysia - Kennedy Aaron Aguol; Jane Wong Kon Ling; Kavitha Ganesan; Anantha Raman Govindsamy; Bernadette Tobi (IPG Kampus Kent, 2021)
Preliminary research on the local knowledge of fishes commonly consumed by Lundayeh ethnic in Lung Pa’ Sia’, Sipitang District, Sabah was conducted. The aim of the study was to identify freshwater species used by Lundayeh ethnic as food resource. In this study, both Matang and Sia’ rivers were fast flowing with clear water and tannin infused water having rocky and sandy substrates. Four families from 16 species were identified. Gastromyzontids represented the majority species frequently caught while High Value Freshwater Table fish Tor species was also consumed by Lundayeh community.